Generation "Z's Perception of Religious Moderation and Tendency to Choose Religious Studies in Indonesia - Abdul Hopid; Sama alee, Abdunrorma; Nur Anisyah Rachmaningtyas; Hanif Cahyo Adi Kistoro (Jurnal Pendidikan Agama Islam, 2023)
Purpose – The purpose of this research is to reveal the potential interest tendency of Gen Z in choosing the theme of religious studies, when Gen Z has an open character but does not want to be bound by a religious system that is too strict based on student experience. Design/methods/approach – This type of research is qualitative research with a phenomenological approach. The focus of this phenomenological research is the researcher's curiosity about students' experiences in behavior and the extent of their perceptions related to the selection of religious studies in successive time series that occur to respondents. Respondents in this study consisted of 40 students from different schools. The respondents were selected by purposive sampling. The data analysis used is based on Bogdan and Biklen's method.    Findings – The experience of students in participating in the study tends to lead to themes that are easy to enjoy such as the theme of fiqh and akhlaq. This diversity shows the openness and openness of this shows the potential for more moderation in religious views and attitudes. Research implications/limitations – Opening up knowledge is related to awareness of the importance of choosing religious studies, especially for the younger generation or known as Gen Z. Therefore, it is important to help teenagers to choose places for religious studies that do not lead to radicalism to the point of destroying proper understanding. Apart from that, the first step to start is through school. Schools should be more responsive and increase their sensitivity regarding student potential. Originality/value – This research still has limitations, especially in collecting the number of respondents. Hopefully future researchers can minimize this deficiency, and subsequent research can be more perfect. Apart from that, future researchers can also measure the extent of religious literacy in students so that the studies that can be given can be measured well.